Effectiveness Of Ethics Of Teaching A Foreign Language Using Information Communication Technologies - Umida Imamova (Euro Asian Journal Publishing, 2024)
The introduction of modern communication technologies into the educational process is the most important issue of their purposeful and correct, effective use, through which the student acquires interest in a foreign language, increases the effectiveness of teaching. This gives access to innovative learning technologies and increases demand
Keywords: communicative methodology; teaching French